Elevated levels of enteric IgA in an unimmunised mouse model of Hyper IgM syndrome derived from gut-associated secondary lymph organs even in the absence of germinal centres - Hernandez-Cazares, Felipe; Maqueda-Alfaro, Raul Antonio; Lopez-Saucedo, Catalina; Martinez-Barnetche, Jesus; Yam-Puc, Juan Carlos; Estrada-Parra, Sergio; Flores-Romo, Leopoldo; Estrada-Garcia, Teresa (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction. Patients with Human Hyper IgM syndromes (HIGM) developed pulmonary and gastrointestinal infections since infancy and most patients have mutations in the CD40 ligand (CD40L) gene. Most HIGM patients vs. healthy subjects have higher/similar IgM and lower IgG, and IgA serum concentrations but gut antibody concentrations are unknown. CD40L on T-activated cells interacts with CD40 on B cells, essential for the formation of germinal centres (GCs) inside secondary lymphoid organs (SLOs), where high-affinity antibodies, long-lived antibody-secreting plasma cells, and memory B cells, are produced. C57-CD40 ligand deficient mice (C57-cd40l−/−), is a model of HIGM, because serum immunoglobulin concentrations are like HIGM patients and have higher faecal IgA concentrations. In mice, SLOs TGFβ and other cytokines induce IgA production. Aims. To compare and evaluate B cell populations and IgA-producing plasma cells in peritoneal lavage, non-gut-associated SLOS, spleen and inguinal lymph nodes (ILN), and gut-associated SLOs, mesenteric lymph nodes (MLN) and Peyer´s patches (PP), of C57-cd40l−/− and C57-wild-type (WT) mice, in the steady-state (not immunised). Material and methods. Eight-10 weeks old C57-cd40l−/− and WT mice, peritoneal lavages were obtained, and PP, MLN, spleen, and ILN SLOs were removed. Organ cryosections were analysed by immunofluorescence and B cell populations and IgA-positive plasma cell suspensions by flow cytometry. Results. At steady-state, GCs WT and C57-cd40l-/- none-gut-associated SLOs lacked GCs. WT gut-associated SLOs harboured GCs but in C57-cd40l-/- SLOs were absent. PP and MLN of C57-cd40l−/− exhibited a significantly higher number of IgA-producing cells vs. WT mice. In C57-cd40l−/− mice. In the spleen and ILN of C57-cd40l−/− mice IgA-producing cells significantly decreased, while IgM-positive plasma cells increased. C57-cd40l−/− B1 cells were more abundant in all analysed SLOs, whereas in WT mice most B1 cells were contained within the peritoneal cavity. C57-cd40l−/− B cells in MLN expressed a higher TGFβ receptor-1 than WT mice. Discussion. Together our results confirm the role of PP and MLN as gut inductive sites, whose characteristic features are to initiate an IgA preferential immune response production in these anatomical sites. IgA antibodies play a pivotal role in neutralizing, eliminating, and regulating potential pathogens and microorganisms in the gut.